2020
DOI: 10.3390/s20226577
|View full text |Cite
|
Sign up to set email alerts
|

Novel Time-Resolved Fluorescence Immunochromatography Paper-Based Sensor with Signal Amplification Strategy for Detection of Deoxynivalenol

Abstract: Immunoassay has the advantages of high sensitivity, high specificity, and simple operation, and has been widely used in the detection of mycotoxins. For several years, time-resolved fluorescence immunochromatography (TRFIA) paper-based sensors have attracted much attention as a simple and low-cost field detection technology. However, a traditional TRFIA paper-based sensor is based on antibody labeling, which cannot easily meet the current detection requirements. A second antibody labeling method was used to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…To label the mAb against A. longipes, Eu (III) chelate nanospheres were chosen due to its high fluorescence intensity, long fluorescence lifetime, and a sharp emission peak at 610 nm which avoids spectra overlap with autofluorescence in real samples (Dong et al, 2020;Tang et al, 2019). It has been reported that Eu (III) nanosphere-conjugated antibody outperforms the same antibody labelled by gold nanoparticles, quantum dots and fluorescein isothiocyanate when detecting E. coli O157:H7 in milk samples, with the highest sensitivity, a wider working range, and better tolerance in real samples (Luo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To label the mAb against A. longipes, Eu (III) chelate nanospheres were chosen due to its high fluorescence intensity, long fluorescence lifetime, and a sharp emission peak at 610 nm which avoids spectra overlap with autofluorescence in real samples (Dong et al, 2020;Tang et al, 2019). It has been reported that Eu (III) nanosphere-conjugated antibody outperforms the same antibody labelled by gold nanoparticles, quantum dots and fluorescein isothiocyanate when detecting E. coli O157:H7 in milk samples, with the highest sensitivity, a wider working range, and better tolerance in real samples (Luo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The universal detection probes were prepared following a procedure by Dong et al 32 100 μL polystyrene fluorescent nanoparticles were added into 400 μL boric acid buffer solution (0.2 M, pH 8.18) and mixed with a vortex oscillator. The mixed solution was ultrasonically treated for 10 min to disperse the polystyrene fluorescent nanoparticles homogeneously in the boric acid buffer solution.…”
Section: Methodsmentioning
confidence: 99%
“…The coated NC film was dried at 37 °C for 2 h before use. The sample pad was treated with blocking solution (2.9 g NaH 2 PO 4 ·12H 2 O, 0.3 g NaH 2 PO 4 ·12H 2 O, 1.0 g PVP-30, 0.5 g BSA, 1.0 g Tween-20 and 0.25 g EDTA were weighed and dissolved in 100.0 mL ultrapure water 32 ) for 15 min, and dried at 37 °C for 2 h. The absorbent pad was used without any treatment. The sample pad, NC membrane and absorbent pad were laminated and pasted on the backing pad successively with an overlap of 1–2 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations